Ley aplicable a los contratos internacionales en el derecho peruano - Monge Talavera, Luz (2021)
The problem of determining the most appropriate law to regulate international contracts has been updated in this health crisis context. This article examines the conflictual regime provided in Peruvian Private International Law. Starting from a comparative approach, it highlights a completely liberal conflict system, which marked, since 1984, a clear detachment from the territorial criteria in force in Latin America. Today, an evaluation of its application shows its limitations.